1989
DOI: 10.1063/1.102159
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxial growth of CdTe and HgCdTe on Si (100)

Abstract: CdTe has been grown on Si(100) by molecular beam epitaxy. Two orientations can be obtained: (111)B CdTe when the CdTe is deposited directly on the Si(100) substrates, and (100)CdTe when an intermediate layer of ZnTe is grown first. The (111)B oriented layers are made of two domains which are rotated by 90°. A layer with only one domain can be grown on Si(100) misoriented by 8°, but the best misorientation for this purpose still needs to be found. These layers were characterized by reflection high-energy electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 14 publications
0
39
0
1
Order By: Relevance
“…Each growth begins with a thick buffer layer consisting of about 1 µm of ZnTe and 8-9 µm of CdTe. Early studies 4,5 have demonstrated that the ZnTe initiation layer is important to preserve the substrate orientation, in the present case the (112)B, before the CdTe layer, which serves to attenuate the propagating threading dislocation density. After the buffer layer, a p-on-n MWIR double-layer heterojunction (DLHJ) having a roomtemperature (RT) cutoff wavelength (λ co ) of about 4.7 µm is grown.…”
Section: Methodsmentioning
confidence: 97%
“…Each growth begins with a thick buffer layer consisting of about 1 µm of ZnTe and 8-9 µm of CdTe. Early studies 4,5 have demonstrated that the ZnTe initiation layer is important to preserve the substrate orientation, in the present case the (112)B, before the CdTe layer, which serves to attenuate the propagating threading dislocation density. After the buffer layer, a p-on-n MWIR double-layer heterojunction (DLHJ) having a roomtemperature (RT) cutoff wavelength (λ co ) of about 4.7 µm is grown.…”
Section: Methodsmentioning
confidence: 97%
“…Each growth began with a buffer layer consisting of about 0.5-lm-thick ZnTe and 7-lm-thick CdTe. Early studies 5,6 demonstrated that the ZnTe initiation layer is important to preserve the substrate orientation; in the present case the crystalline orientation is (112)B, before the CdTe layer, which serves to attenuate the propagating threading dislocations. After the buffer layer, the detector structure is grown.…”
Section: Methodsmentioning
confidence: 96%
“…Crystal quality has improved dramatically since 1989, when single crystalline CdTe(111)B was first grown on Si(001) by MBE, with the demonstration that a ZnTe buffer layer can be used to preserve the homo-orientation of CdTe/Si. 5 Due to the large lattice mismatch of 5.5% and the huge thermal mismatch of 266% between CdTe and PbSnSe, large strain near the interface between PbSnSe and CdTe is expected. We show that the strain can be released by a series of imperfect glide dislocations.…”
Section: Introductionmentioning
confidence: 99%